Pengaruh Motivasi Belajar terhadap Pemahaman Konsep Matematis Melalui Self-Regulated Learning dan Kemampuan Numerasi - Mutammimah, Siti; Rukmigarsari, Ettie; Sufyan Zauri, Ahmad (Program Studi Pendidikan Matematika FIP UNHASY, 2026)
This study was motivated by the condition of VII students who had just entered junior high school and still experienced difficulties in understanding mathematics learning. Based on information from the mathematics teacher, mathematics was often considered a difficult subject, which caused students to have low motivation and enthusiasm in learning and to be less serious in solving mathematical problems. This condition led students to answer questions randomly without going through an appropriate thinking process. This study aimed to determine the effect of learning motivation on students’ mathematical conceptual understanding through self-regulated learning and numeracy skills among seventh-grade students at SMP Qur’an Ar-Roudloh. The study used a quantitative approach with an observational (expost facto) method. The research subjects consisted of 65 seventh-grade students from classes VII-A, VII-D, and VII-E who were selected using a cluster random sampling technique. Data were collected through questionnaires and tests, and subsequently analyzed using path analysis with the assistance of software SPSS 25 and software SmartPLS 4.0. The results showed that learning motivation had a direct effect on self-regulated learning with a coefficient of 0.781, a direct effect on numeracy skills of 0.441, and a direct effect on mathematical conceptual understanding of 0.375. In addition, self-regulated learning had a direct effect on numeracy skills of 0.447 and on mathematical conceptual understanding of 0.260, while numeracy skills had a direct effect on mathematical conceptual understanding of 0.365. These findings indicated that learning motivation played an important role in improving students’ mathematical conceptual understanding both directly and indirectly through self-regulated learning and numeracy skills.